Reaction of 1-Lithio (Phenylsulfinyl) - Cyclopropane with Electrophiles: An Alternative Synthesis of 1-Alkyl-And L-(L-Hydroxyalkyl)-(Phenylsuslfinyl) Cyclopropanes - Manat Pohmakotr (2018)
The reaction of 1-lithio (phenylsulfinyl)cyclopropane with various electrophiles was studied. The reductive deoxygenation of the resulting adducts with TiCl^/Zn provided 1-substituted (phenylsulfinyl)cyclopropanes. © 1989, Taylor & Francis Group, LLC. All rights reserved.